Nano Fe3O4-activated carbon composites for aqueous supercapacitors - M.Y., Ho; P.S., Khiew; Isa, D.; T.K., Tan; W.S., Chiu; C.H., Chia; Hamid, M.A.A.; Shamsudin, R. (Universiti Kebangsaan Malaysia, 2014)
In this study, a symmetric supercapacitor has been fabricated by adopting the nanostructured iron oxide (Fe3O4)-activated carbon (AC) composite as the core electrode materials. The composite electrodes were prepared via a facile mechanical mixing process and PTFE polymeric solution has been used as the electrode material binder. Structural analysis of the nanocomposite electrodes were characterized by scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET) analysis. The electrochemical performances of the prepared supercapacitor were studied using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) in 1.0 M Na2SO3 and 1.0 M Na2SO4 aqueous solutions, respectively. The experimental results showed that the highest specific capacitance of 43 F/g is achieved with a fairly low Fe3O4 nanomaterials loading (4 wt. %) in 1 M Na2SO3. It is clear that the low concentration of nanostructured Fe3O4 has improved the capacitive performance of the composite via pseudocapacitance charge storage mechanism as well as the enhancement on the specific surface areas of the electrode. However, further increasing of the Fe3O4 content in the electrode is found to distort the capacitive performance and deteriorate the specific surface area of the electrode, mainly due to the aggregation of the Fe3O4 particles within the composite. Additionally, the CV results showed that the Fe3O4/AC nanocomposite electrode in Na2SO3 electrolyte exhibits a better charge storage performance if compared with Na2SO4 solution. It is believed that Fe3O4 nanoparticles can provide favourable surface adsorption sites for sulphite (SO32-) anions which act as catalysts for subsequent redox and intercalation reactions.